Machine learning : hands-on for developers and technical professionals - Bell, Jason (Computer scientist) (ITpro collection, 2020)
Dig deep into the data with a hands-on guide to machine learning. 'Machine Learning' provides hands-on instruction and fully-coded working examples for the most common machine learning techniques used by developers and technical professionals.